Assessment of Peri-Implant Soft Tissues Conditions around Short and Ultra-Short Implant-Supported Single Crowns: A 3-Year Retrospective Study on Periodontally Healthy Patients and Patients with a History of Periodontal Disease - Lombardo, Giorgio (Int J Environ Res Public Health, 2020)
The aim of this retrospective study was to evaluate implant survival, marginal bone loss and peri-implant complications in 326 short and ultra-short implants. Implants were placed in the maxillary and mandibular posterior regions of 140 patients with (PP) and without (NPP) a history of periodontal disease. Clinical and radiographic examinations were performed at 3-year recall appointments. The 8.0, 6.0 and 5.0 mm-length implants placed in PP and NPP were respectively 43.75% and 38.46%, 35.10% and 34.19%, 21.15% and 27.35%; 325 implants (one early failure) were rehabilitated with single crowns in 139 patients. Overall implant survival after 3 years of follow-up was 97.55%, 98.08% and 96.61% for PP and NPP (p = 0.46). Crestal bone level variations were not statistically different among PP and NPP; 15.41% of implants presented signs of mucositis, 14.71% and 16.67% in PP and NPP (p = 0.64). Setting the threshold for bone loss at 2 mm after 36 months, peri-implantitis prevalence was 2.2%, 1.96% and 2.63% in PP and NPP (p = 0.7). Overall implant success was 82.39%, 83.33% and 80.7% for PP and NPP (p = 0.55). Short-term outcomes suggest that short and ultra-short locking-taper implants can successfully be restored with single crowns in the posterior jaws both in PP and NPP.